Challenges and Strategies in Translating English Collocations into Kurdish: A Linguistic Approach - Hama Amin, Zana (Language, Technology, and Social Media, 2023)
Collocation is a combination of two or more words which always arbitrarily come together in different contexts in language. This research deals with the translation of English collocations into Kurdish. The aim of this study is to introduce those problems that Kurdish students encounter when they translate English collocations into Kurdish and then how to solve them. This paper is divided into two main sections. The first section discusses categorizations of collocation and its translation into Kurdish: problems and solutions. In the second section, there is an empirical study to hypothesize that Kurdish students face difficulties in translating English collocations into Kurdish. This research uses qualitative and quantitative methods. The test involves twenty students of fourth year in the Department of English-College of Languages-University of Sulaimani. The results of the test come up with the hypothesis of the study.